The teacher's funeral : a comedy in three parts - Peck, Richard, 1934-2018 (Puffin Books, 2006)
In rural Indiana in 1904, fifteen-year-old Russell's dream of quitting school and joining a wheat threshing crew is disrupted when his older sister takes over as the teacher at his one-room schoolhouse after mean old Myrt Arbuckle "hauls off and dies." Russell and his friends are more determined than ever to close the school, even if it means stealing, setting the outhouse on fire, and bringing snakes to class.